Effect of dietary cation-anion balance on growth performance of broiler chicken - Mary Juliet Francis (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 2005)
An investigation over a period of six weeks was carried out to study the effect of dietary cation-anion balance on growth performance of broiler chicken. One hundred and sixty commercial day-old broiler chicks were randomly allotted to four dietary treatments viz., T1, T2, T3 and T4 having four replicates each. The experimental diets were standard broiler ration with varying DCAB of 260 meq/kg (T1, control), 210 meq/kg (T2), 310 meq/kg (T3) and 360 meq/kg (T4). Cation-anion balance was varied using sodium bicarbonate and ammonium chloride. Results indicated that the dietary treatments did not differ significantly in body weight, weight gain, feed conversion ratio, feed intake, water consumption and processing yields. Body weight at the end of six weeks was 2069, 2031, 2047 and 2020 g and the cumulative mean body weight gain was 2023, 1984, 2000 and 1973 g for T1, T2, T3 and T4, respectively. Average daily feed intake was 159.39, 164.46, 166.65 and 169.81 g and mean cumulative FCR were 2.04, 2.02, 2.04 and 2.09, respectively, for T1, T2, T3 and T4. No significant difference was observed in serum minerals or biochemical parameters such as serum uric acid, cholesterol and glucose. Birds in T3 and T4 showed significantly higher (P<0.05) intake and balance of sodium than T1 and T2. Retention of chloride was significantly higher (P<0.05) for T3 and T4 whereas chloride intake was significantly lower (P<0.05) for T3 and T4. Overall evaluation of the results of the present study reveals that dietary cation-anion balance does not have a significant influence on growth performance of broiler chicken.